Detection of CD133-marked cancer stem cells by surface plasmon resonance: Its application in leukemia patients - Fathi, Farzaneh; Rahbarghazi, Reza; Movassaghpour, Ali Akbar; Rashidi, Mohammad-Reza (Biochimica et biophysica acta. General subjects, 2019)
Here, we reported the development of a label-free and real-time surface plasmon resonance (SPR) based biosensor for cancer stem cells (CSCs) detection using cell surface biomarker; CD133. The fabricated biosensor was used for detection of this marker in some acute myeloid leukemia (AML) patients and the results were compared with those obtained from flow cytometry (FC) method. CD133 antibody was immobilized on the gold chip surface via EDC/NHS coupling method and binding of the candidate cells to the modified gold sensor surface was monitored after isolation of mononuclear cells from bone marrow of the patients. The method was validated in terms of various parameters such as CD133- antibody concentration and cell density. The CD133-marked cells were investigated in seven AML patients. All SPR results were compared with those obtained from FC method. A very good correlation (R2 = 0.96) was obtained between SPR and FC responses related to CD133-marked cells densities. In conclusion, in this study, a label-free and real-time SPR cytometry method was developed to detect CD133 and it was successfully applied to follow this cancer stem cell biomarker in AML patients. [Display omitted] •SPR-based method was developed for detection of CD133+ cancer stem cells in patients with AML.•SPR was validated by using CD133 antibody concentrations and cell density.•A strong correlation was obtained between SPR and flow cytometry responses.